Dual Returns to Experience - Jose Garcia-Louzao; Laura Hospido; Alessandro Ruggieri (Institute of Labor Economics (IZA), 2021)
In this paper we study human capital accumulation and wage trajectories of young workers in a dual labor market. Using rich administrative data for Spain, we follow workers since labor market entry to measure experience accumulated under different contractual arrangements and relate it to current wages. We show that returns to experience accumulated in fixed-term contracts are, on average, lower than the returns to experience acquired in permanent jobs. However, this gap masks significant heterogeneity across individuals. The gap in returns widens along the skill distribution, where workers in the upper tail have the largest difference in returns. Moreover, among equally experienced workers, higher incidence of temporary employment in the past is associated with substantially lower wages. Ultimately, heterogeneous returns to experience translate into significant changes in the position of workers along the distribution of wage growth after 15 years in the labor market, bearing implications for life-cycle wage inequality.
Keywords: J30; J41; J63; 330; human capital; labor market duality; earnings dynamics